The Effect of Teacher Candidates’ Perceptions of Their Initial Teacher Education Program on Teaching Anxiety, Efficacy, and Commitment - Daniels, Lia M.; Mandzuk, David; Perry, Raymond P.; Moore, Ceri (Alberta Journal of Educational Research, 2011)
In a novel approach to initial teacher education, we combined a program review perspective and a psychological perspective. First, we assessed the extent to which student teachers (n=137) felt that components of their BEd program prepared them for teaching and whether these components represented meaningful program dimensions. Through content analysis, exploratory factor analysis, and teacher candidates’ own words, five dimensions emerged: classroom dynamics; curriculum, instruction, and assessment; intrapersonal reflection; ethics of teaching; and professional learning community. Second, we tested how each of these dimensions predicted teaching anxiety, efficacy, and commitment. The results from regression analyses showed that ethics of teaching was the most influential dimension by decreasing anxiety and increasing efficacy and commitment. Results are discussed in terms of the effect of initial teacher education program dimensions on the psychosocial development of teacher candidates. Adoptant une approche novatrice à la formation initiale des enseignants, nous avons combiné une perspective visant l'examen des programmes avec une perspective psychologique. Nous avons d'abord évalué la mesure dans laquelle les stagiaires (n=137) estimaient que des composantes de leur programme d'études (B.Ed.) les avaient préparés pour l'enseignement et à quel point ces composantes représentaient des dimensions significatives de leurs programmes. Cinq dimensions ont découlé des analyses du contenu, des facteurs exploratoires et des propres paroles des stagiaires : la dynamique en salle de classe; le programme d’étude, l’enseignement et l’évaluation; la réflexion intrapersonnelle; l’éthique et l’enseignement; et les communautés professionnelles d’enseignement. Nous avons ensuite évalué dans quelle mesure chacune de ces dimensions constituait une variable explicative de l’anxiété, l’efficacité et l’engagement en enseignement. Les résultats sont présentés en fonction de l’effet des dimensions du programme de formation initiale des enseignants sur le développement psychosocial des stagiaires.